Business Valuation Transformation of Innovative Products Through Scenario Analysis (Case Study: Sakasea) - Nurhakim Siswanto; Nimmi Zulbainarni; Suhendi (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Valuing early-stage innovative products is challenging because limited operating history makes valuation highly sensitive to uncertainty in market uptake and production scale, particularly under tight competition. Sakasea currently operates below its break-even scale, resulting in negative cash flows under baseline conditions. This study applies a single-case design to Sakasea using internal operational and financial records to conduct baseline valuation and scenario-based projections.Purpose: This study aims to demonstrate how scenario-based analysis can transform the valuation of an innovative food product, Sakasea, from an initially unfeasible condition into a feasible and profitable business projection.Design/methodology/approach: A quantitative single-case study was applied (n = 1, Sakasea). Baseline (actual) valuation was conducted using eight financial feasibility indicators (R/C Ratio, ROI, BEP, NPV, IRR, BCR, PI, and Payback Period) based on internal operational and financial records. Two scenario projections (Realistic and Optimistic) were then constructed by adjusting the key driver of production and sales volume over a five-year horizon, followed by re-evaluation using the same indicators.Findings/Result: The actual (baseline) valuation indicates financial infeasibility (NPV = IDR –583,427,867; BCR = 0.17; IRR = N/A due to negative cash flows; Payback Period not achieved). Under the Realistic scenario, the valuation becomes feasible (NPV = IDR 188,085,414; IRR = 36.27%; BCR = 1.27; Payback Period = 1.49 years). Under the Optimistic scenario, feasibility improves further (NPV = IDR 682,595,444; IRR = 46.69%; BCR = 1.52; Payback Period = 0.57 years).Conclusion: Static valuation based solely on initial operations may underestimate early-stage innovations. Scenario-based valuation provides a forward-looking assessment by illustrating how feasibility changes as production scale increases beyond the break-even threshold.Originality/value (State of the art): This study provides empirical evidence on scenario-based valuation of an early-stage functional food innovation by quantifying how key feasibility indicators (NPV, IRR, BCR, and payback period) shift from baseline to scale-up conditions, thereby identifying the production scale required for financial viability. Keywords:  business valuation, discounted cash flow, financial feasibility, innovative product, scenario analysis